2010
DOI: 10.1177/0960327110361753
|View full text |Cite
|
Sign up to set email alerts
|

Over 8 years experience on severe acute poisoning requiring intensive care in Hong Kong, China

Abstract: In order to obtain up-to-date information on the pattern of severe acute poisoning and the characteristics and outcomes of these patients, 265 consecutive patients admitted to an intensive care unit in Hong Kong for acute poisoning from January 2000 to May 2008 were studied retrospectively. Benzodiazepine (25.3%), alcohol (23%), tricyclic antidepressant (17.4%), and carbon monoxide (15.1%) were the four commonest poisons encountered. Impaired consciousness was common and intubation was required in 67.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
59
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 20 publications
(28 reference statements)
14
59
1
6
Order By: Relevance
“…According to the pertinent literature, the ratio of females are slightly higher than males in acute poisonings [1,2,7,6]. Şencan et al [1] reported a female to male ratio of 1.2/1, and that data was similar to the result that obtained in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to the pertinent literature, the ratio of females are slightly higher than males in acute poisonings [1,2,7,6]. Şencan et al [1] reported a female to male ratio of 1.2/1, and that data was similar to the result that obtained in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Poisoning, which is a frequent medical emergency requiring treatment at intensive care units, is the most important cause of morbidity and death observed at intensive care units [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Şencan et al (17), 21% of the 55 organophosphate cases died, and the highest rate was methanol intoxication with 54.5% of the 11 cases. Furthermore, in the study conducted by Lam et al (18), 5 of the 8 patients died in the intensive care unit; of these, 1 died because of multiple organ failure developed as a result of thinner + paracetamol intoxications, 1 died because of brain death developed as a result of carbon monoxide intoxication, 1 died because of cardiac arrest developed as a result of dothiepin + paracetamol intoxication, 1 died because of amphetamine + alcohol, and 1 died because of lithium + chlorpromazine + alcohol intoxications that caused brain edema. Singh et al (19) have reported that 3 cases died due to aluminum phosphide intoxication; all 3 patients died during mechanical ventilator support because of refractory hypotension unresponsive to vasopressor drugs, metabolic acidosis, and respiratory failure.…”
Section: Discussionmentioning
confidence: 96%
“…The outcome in hospital care is good even with the cases treated in the intensive care unit (ICU) with the mortality rate less than 3%, [1][2][3][4] and in a Norwegian study by Lund et al the hospital mortality was even less, 0.8%. 5 The hospital length of stay (LOS) is usually less than one day.…”
Section: Introductionmentioning
confidence: 99%
“…5 The hospital length of stay (LOS) is usually less than one day. [1][2][3][4][5] The causes of intoxication include analgesics and psychotropic drugs, such as antidepressants and anxiolytics. 1,5 In Finland the most typical cause of acute drug poisoning is the intake of psychotropic products in association with alcohol intoxication.…”
Section: Introductionmentioning
confidence: 99%